The genus Leucotabanus Lutz (Diptera: Tabanidae) in the Amazon region, with the description of a new species - Henriques, Augusto L.; Krolow, Tiago K. (Zootaxa, 2019)
The Leucotabanus species with records in the Amazon are reviewed. Seven species are included: L. albovarius, L. exaestuans, L. flavinotum, L. janinae, L. pauculus, L. weyrauchi, and L. fairchildi n. sp., which is described herein. The male of L. weyrauchi is described for the first time. Another two non-Amazonian species, L. canithorax and L. sebastianus, were compared, illustrated, and discussed, with new distribution records for the latter species. A key for the seven Leucotabanus species found in the Amazon, along with diagnoses, discussions, distributions and illustrations, are presented.